Navigating formula shortages: associations of parental perspectives on transitioning to alternative infant formulas for cow's milk protein allergy during the 2022 national formula shortage - Fabbrini, Abigail L.; Farrar, Andrew A.; Brown, Jerry M.; Oliveros, Lea V.; Florio, Jared; Beacker, Jesse; Lamos, Luke; Baran, Jessica V.; Wilsey, Michael J. (Frontiers in Allergy, 2024)
The COVID-19 pandemic led to supply chain disruptions causing a severe shortage of infant formula. The shortage impacted parents of infants with cow's milk protein allergy (CMPA) who rely on specialized formulas. However, research on parent perspectives during formula shortages is limited. We aimed to understand the factors guiding parents' decisions when transitioning to alternative amino acid formula (AAF) or extensively hydrolyzed formula (eHF) during the national formula shortage. We conducted a survey using the ZSMoments platform and found that before the shortage, parents valued safety (83%), tolerability (78%), and reputability (78%) as primary factors in selecting eHFs and AAFs. Post-shortage, formula tolerability (86%), assurance (84%), and safety (80%) gained more importance. Among those switching eHF (n=54), health care provider recommendations (81%), reputability (78%), taste (78%), and tolerability (78%) were rated as "extremely important." Among those switching AAF (n=26), top factors included tolerability (77%), assurance (73%), safety (73%), cost-effectiveness (73%), and formula trustworthiness (73%). These data suggest that parents carefully weigh various factors when managing their child's CMPA and transitioning to different AAF or eHF options.